Co-invasion of invasive trees and their associated belowground mutualists - Nuñez, Martin Andres (2016)
The majority of trees need mutualistic associations to thrive and survive. This can be a fundamental limitation for their ability to colonise new areas and consequently invade them. While many non-native tree species may form associations with local mutualists that substitute those present in their native range, others, probably with a higher degree of specialisation invade along with their native range mutualists (co-invade). An example of this is the case of some figs (Ficus spp.); in the USA, these trees which have a highly specialised pollination system depending on particular species of wasps, became invasive only after their native pollinator had arrived (Richardson et al. 2000). Other examples can be found in many invasive trees that need belowground mutualists, like nitrogen-fixing symbionts and mycorrhizal fungi, to thrive in their new geographical range (e.g. Nuñez et al. 2009, Dickie et al. 2010). These soil mutualists have been found to play a key role on the invasion of numerous introduced tree species (Nuñez and Dickie 2014)...